2011
DOI: 10.1177/1045389x11411121
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a Span-Extending Morphing Wing

Abstract: Recent developments in morphing aircraft research have motivated investigation into conformal morphing systems, that is, shape change without discrete moving parts or abrupt changes in the airfoil profile. In this study, implementation of a continuous span morphing wing is described. The system consists of two primary components: (1) zero-Poisson ratio morphing core and (2) fiber-reinforced elastomeric matrix composite skin with a nearly zero-Poisson ratio in-plane. The main goal for improved air vehicle effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 20 publications
0
76
0
Order By: Relevance
“…22 Though these advanced blade shapes are static, feasibility of dynamic shape changing skin technologies has been proven for one-dimensional structures 23,24,25 and airfoil structures. 26,27 Hence, it appears that the maturity of these types of components has progressed to a level where design for fabrication and testing on a rotorcraft system is possible. Herein, shape-changing rotor blades could be designed to account for the conflicting requirements of advancing and retreating blades, approaching an aerodynamic optimum, or to change configuration for optimal hover or forward flight performance.…”
Section: Introductionmentioning
confidence: 98%
“…22 Though these advanced blade shapes are static, feasibility of dynamic shape changing skin technologies has been proven for one-dimensional structures 23,24,25 and airfoil structures. 26,27 Hence, it appears that the maturity of these types of components has progressed to a level where design for fabrication and testing on a rotorcraft system is possible. Herein, shape-changing rotor blades could be designed to account for the conflicting requirements of advancing and retreating blades, approaching an aerodynamic optimum, or to change configuration for optimal hover or forward flight performance.…”
Section: Introductionmentioning
confidence: 98%
“…In general, morphing aircraft is developed to increase vehicle performance by changing their external shapes during flight. 1 Morphing on a larger scale that involves significant changes in the camber, 2-4 wing span, [5][6][7] twist, 8,9 or sweep 10,11 has been profoundly investigated since the early 90's with NASA's Morphing Project. 12 A recent review on morphing aircraft, focusing on structural active morphing concepts, can be found in Barbarino.…”
Section: Introductionmentioning
confidence: 99%
“…Applications for morphing aircraft (Vocke III et al 2011) based on SMAs are of great scientific interest. The lifting surfaces of current aircraft are designed as a 'compromise' geometry that allows the aircraft to fly in a range of flight conditions, but the performance in each condition is likely to be sub-optimal.…”
Section: Introductionmentioning
confidence: 99%